Jan Długosz jako kronikarz dziejów Podniestrza w I połowie XII wieku - Benyskiewicz, Krzysztof (In Gremium. Studies in History, Culture and Politics, 2016)
JAN DŁUGOSZ AS CHRONICLER OF THE HISTORY OF THE PODNIESTNE REGION IN THE 1ST HALF OF THE 12TH CENTURY The article Jan Długosz as chronicler of the history of the Podniestrze region in the 1st half of the 12th century presents an analysis of the message contained in Długosz’s Annals dealing with the political situation in the south-eastern borderland of Rus’ and with the political and dynastic contacts between those ruling there and the Piast dynasty. The Annals of Jan Długosz represent an important source of information about Rus’ history as well as about the relations between Poland and Rus’ in the Middle Ages. In the light of the information provided in the Annals the history of region of Podniestrze during the rule of Rostislav of Tmutarakan’s descendants seem especially interesting. The very essence of Długosz’s reports is based on the fact that Długosz became a depositary of information which cannot be found in any other sources identified so far. The analysis of the information provided by Długosz has been made for separate checkpoints at three levels mentiod above. With respects to the internal situation – the conflicts in Podniestrze, the author notes, that Długosz’s description is a paraphrase of information taken from Rus’ chronicles and parts of documents of unknown origin. The 15th century’s chronicler’s reports on the border fights between Poland and the region of Peremyshl (Przemyśl) as well as mutual destructive invasions must be interpreted in a similar way. As a result, the whole cycle of the reports concerning Peremyshl contained in the Annals from the period 1122-1128 raises doubts as to the reliability of the information provided. The article refers also to the genealogical information provided by Długosz. Particular attention is given to the Duke Ivan, the alleged son of the Knyaz of Trembovla, Vasili Rostislavits. Długosz’s reference to this ruler’s existence is the only known mention. It seems to be a fictitious figure we are dealing with in this case. The strict assessment of the information by Jan Długosz in the concerning the parts covered by the analysis, results from the fact that it is not confirmed in any other source as well from the specificity of the reconstruction undertaken by the chronicler. Confabulation remains a significant element of this reconstruction. Particular attention should be drawn to Długosz’s creation of a new reality by a random combination of facts originally belonging to different realities.